A New Approach of Optimal Search Solution in Particle Swarm Optimization (PSO) Algorithm for Object Detection Method - Zalili, Musa; Mohd Hafiz, Mohd Hassin; Nurul Izzatie Husna, Fauzi; Rohani, Abu Bakar; Watada, Junzo (American Scientific Publisher, 2018)
In video tracking system, the big data era has brought with it new challenges to computer vision and image understanding. The main challenges are using the conventional method is the uncertainty in the accuracy and precision of the detected object motion. Furthermore, the process of detected an object in every frame is time consuming as the entire frame must be detected to precisely locate the object system. Therefore, to overcome the several problems associated with the object detection method, a new approach in Particle Swarm Optimization (PSO) algorithm for optimal search solution as an alternative method to detect of object tracking quickly, precisely and accurately. Finally, performance analysis will be undertaken to justify the strength of the proposed method over conventional algorithm can reduce more than 60% of the required number of particles and iteration.